2021
DOI: 10.1002/anie.202101906
|View full text |Cite
|
Sign up to set email alerts
|

Double‐Exchange‐Induced in situ Conductivity in Nickel‐Based Oxyhydroxides: An Effective Descriptor for Electrocatalytic Oxygen Evolution

Abstract: Motivated by in silico predictions that Co,Rh, and Ir dopants would lead to low overpotentials to improve OER activity of Ni-based hydroxides,wereport here an experimental confirmation on the altered OER activities for as eries of metals (Mo,W ,F e, Ru, Co,Rh, Ir) doped into g-NiOOH. The in situ electrical conductivity for metal doped g-NiOOH correlates well with the trend in enhanced OER activities. Density functional theory (DFT) calculations were used to rationalizethe in situ conductivity of the key interm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(86 citation statements)
references
References 61 publications
4
75
0
Order By: Relevance
“…Ideal catalysts for OER it is expected to have: (i) as high as possible number of active sites along with possible large specific surface area (SSA) enlarging obtained anode current densities and facilitating charge and oxygen species transfer, (iii) high electrical conductivity, (iv) chemical, electrochemical and mechanical stability, (v) as low as possible intrinsic overpotentials during water splitting reactions [40] . Therefore, we strongly believe that the Ni@C−(N)CNF‐5 has a potential to meet the requirements for an excellent electrocatalyst for water splitting, due to its outstanding properties, such as: (i) layered structure, which is favorable for charge transfer, [41] (ii) presence of Ni with high theoretical OER activities according to the Volcano‐shaped relationship, [42] ability to redox transition [43] as well as its conductive nature [44] . To verify it detailed electrochemical characterization as electrocatalyst in OER has been conducted and presented below.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ideal catalysts for OER it is expected to have: (i) as high as possible number of active sites along with possible large specific surface area (SSA) enlarging obtained anode current densities and facilitating charge and oxygen species transfer, (iii) high electrical conductivity, (iv) chemical, electrochemical and mechanical stability, (v) as low as possible intrinsic overpotentials during water splitting reactions [40] . Therefore, we strongly believe that the Ni@C−(N)CNF‐5 has a potential to meet the requirements for an excellent electrocatalyst for water splitting, due to its outstanding properties, such as: (i) layered structure, which is favorable for charge transfer, [41] (ii) presence of Ni with high theoretical OER activities according to the Volcano‐shaped relationship, [42] ability to redox transition [43] as well as its conductive nature [44] . To verify it detailed electrochemical characterization as electrocatalyst in OER has been conducted and presented below.…”
Section: Resultsmentioning
confidence: 99%
“…[40] Therefore, we strongly believe that the Ni@CÀ (N)CNF-5 has a potential to meet the requirements for an excellent electrocatalyst for water splitting, due to its outstanding properties, such as: (i) layered structure, which is favorable for charge transfer, [41] (ii) presence of Ni with high theoretical OER activities according to the Volcano-shaped relationship, [42] ability to redox transition [43] as well as its conductive nature. [44] To verify it detailed electrochemical characterization as electrocatalyst in OER has been conducted and presented below.…”
Section: Electrocatalytic Oxygen Evolution Reactionmentioning
confidence: 99%
“…In addition to the Ni-based oxyhydroxides, DE interaction has been recently proposed to boost the OER performance in other systems such as spinel oxides. [33] Moreover, spectroscopic studies also suggested the surface reconstructed oxyhydroxides to be a general intermediate OER active phase in metal nitrides, [18b] spinel oxides and perovskites, [34] metal-organic frameworks, [35] where internal DE interaction might also exist and contribute to the OER activity. Therefore, the DE-induced transport indicator, enabled by on-chip in situ measurements demonstrated in this work, can potentially help elucidate the OER mechanisms in various classes of inorganic materials, where the mixed valence metal oxyhydroxide plays an essential role in the electro-oxidative process.…”
Section: Research Articlementioning
confidence: 99%
“…H 2 ) and OER (4OH À !O 2 + 2H 2 O) by applying electrocatalysts to produce hydrogen and oxygen. [2] Currently, although noble metal-based materials (such as Pt, RuO 2 and IrO 2 ) are the most advanced catalysts, [3] the prohibitive expense and scarcity severely hinder their largescale application. [4] Therefore, it is impending to exploit the catalysts with high-efficiency and affordable to reduce overpotential and improve water splitting efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…The environmental problems and energy crisis caused by excessive use of fossil fuels have led to the demand for renewable energy technologies [1] . Electrochemical water splitting is a primary step towards sustainable clean energy to accelerate the HER (2H + +2e − → H 2 ) and OER (4OH − →O 2 +2H 2 O) by applying electrocatalysts to produce hydrogen and oxygen [2] . Currently, although noble metal‐based materials (such as Pt, RuO 2 and IrO 2 ) are the most advanced catalysts, [3] the prohibitive expense and scarcity severely hinder their large‐scale application [4] .…”
Section: Introductionmentioning
confidence: 99%